Peningkatan Fungsi Kognitif Lansia Melalui Terapi Aktivitas Kognitif - Freny Ravika Mbaloto; Estelle Lilian Mua; Robi Adikari Sekeon; Denny Susanto; Ida Yanriatuti; Sabarulin Tarigan; Ni Luh Emilia (Indonesian Scientific Journal, 2023)
Abstract: In general, the older a person is, the more susceptible they are to experiencing a decline in function, including cognitive function. The condition that often occurs in the elderly is a decrease in the ability to remember so that they often forget easily. Reduced cognitive function in the elderly is an early manifestation of dementia. Decreasing cognitive function in the elderly causes an increase in cognitive function disorders such as dementia which affects the ability to meet daily needs and a high degree of dependence on others. The elderly can fill their declining cognitive abilities by optimizing themselves through cognitive activities. Based on this, community service has been carried out targeting the elderly at PWST Tresno Mukti Turen. Through community service it is hoped that it can improve the cognitive function of the elderly. The implementation of this community service uses the method of assessment, observation, interviews, demonstrations. During the therapy, the elderly seemed enthusiastic about participating in all the activities. Cognitive therapy is effective in improving the cognitive function of the elderly if it is carried out routinely and scheduled in the daily activities of the elderly Abstrak: Pada umumnya semakin bertambah usia seseorang maka semakin rentan mengalami penurunan fungsi termasuk fungsi kognitif. Keadaan yang kerapkali terjadi pada lansia adalah menurunnya kemampuan mengingat sehingga sering akan mudah lupa. Berkurangnya fungsi kognitif pada lansia merupakan manifestasi awal demensia. Penurunan fungsi kognitif pada lansia menyebabkan peningkatan gangguan fungsi kognitif seperti demensia yang berdampak terhadap kemampuan memenuhi kebutuhan sehari-hari dan tingkat ketergantungan yang tinggi terhadap orang lain. Lansia dapat mengisi kemampuan kognitif mereka yang menurun dengan mengoptimalkan diri mereka sendiri melalui aktivitas kognisi. Berdasarkan hal tersebut telah dilakukan pengabdian kepada masyarakat dengan sasaran lansia di PWST Tresno Mukti Turen. Melalui pengabdian kepada masyarakat diharapkan dapat meningkatkan fungsi kogntif lansia. Pelaksanaan pengabdian masyarakat ini menggunakan metode pengkajian, observasi, wawancara, demonstrasi. Saat terapi berlangsung, para lansia tampak antusias mengikuti seluruh rangkaian kegiatan. Terapi kognitif efektif dalam meningkatkan fungsi kognitif lansia jika dilaksanakan rutin dan dijadwalkan dalam aktivitas keseharian lansia